Mental health and quality of life among Veterans: the role of prayer/meditation and faith in God/higher power - Switzer, Jennifer (My University, 2025)
The aim of this study is to better understand the role of spirituality in reducing the adverse effects of mental health conditions on Veterans’ quality of life. The study explored which aspects of spirituality – rituals or faith in God/Higher Power – were associated with mental health conditions and if spirituality mediated the relationship between mental health conditions and Veterans’ quality of life. Participants included 1048 military Veterans in the U.S. Structural equation modeling was utilized to test the proposed mediation model. The results indicated that depression and anxiety were correlated with less engagement in prayer/meditation and greater faith in God/Higher Power. Trauma was correlated with more engagement in prayer/meditation and greater faith in God/Higher Power. Suicidal risk was correlated with greater faith in God/Higher Power. Results of indirect effects suggested that prayer/meditation had the potential to reduce the adverse effects of trauma but not depression or anxiety on quality of life. No indirect effects were found for faith in God/Higher Power. The results have implications for clinical practice and future research.
Keywords: Mental health; Veterans; Spirituality